Implantable Multifunctional Micro‐Oxygen Reservoir System for Promoting Vascular‐Osteogenesis via Remodeling Regenerative Microenvironment - Min Rui; Jiannan Mao; Hongshuai Wu; Yujian Hui; Hao Shen; Yilin Yang; Tao Ma; Kewei Ren; Juan Wang; Wenguo Cui; Qin Shi; Huilin Yang (Advanced Science)
Abstract Hypoxia and reactive oxygen species (ROS) overaccumulation cause persistent oxidative stress and impair intrinsic regenerative potential upon tissue injury. For local tissue injury with hypoxia, such as bone fracture and defects, a localized‐sufficient oxygen supply is highly desirable but remains challenging. Therefore, to explore a strategy and its intrinsic mechanism for supplying oxygen locally and remodeling the regenerative microenvironment, an innovative oxygenating hydrogel microsphere system with sustained oxygenation and antioxidant properties is introduced by loading CaO2@SiO2@PDA (CSP) nanoparticles. Specifically, the CSP nanoparticles exhibited broad‐spectrum free radicals scavenging ability, along with prolonged controlled‐release of oxygen once integrated into the gelatin methacrylate anhydride (GelMA) microspheres (CSP‐GM). The CSP‐GM with extra cellular matrix (ECM)‐mimicking structures reconstructed living niches, promoting the adhesion and proliferation of bone marrow stromal cells (BMSCs). As a multifaceted microenvironment regulator, CSP‐GM remodeled the regenerative microenvironment by synergistically producing oxygen and scavenging ROS, recovering mitochondrial homeostasis and antioxidant defenses of BMSCs, promoting angiogenesis and osteogenesis under hypoxia conditions via precisely modulating the Nrf2/HO‐1 signaling pathway. The multiple pro‐regenerative effects of the implantable functionalized micro‐oxygen reservoir on bone repair are further corroborated by the enhanced vascularized bone formation in rat femoral defects, presenting a comprehensive and promising strategy for tissue repair.